Low resolution fourier synthesis modelling for underwater acoustic channel impulse response. (January 2022) - An, Liang; Qiu, Yifeng; Wang, Xiaoyan; Zhang, Long; Huang, Ran
Abstract: Fourier synthesis is the most widely used method for underwater acoustic broadband modeling. Traditionally, high frequency resolution and large time window length are needed to generate broadband time series to avoid aliasing in time domain. An optimized Fourier synthesis method is presented in this paper to accelerate the impulse response function modelling. The method consists of two steps, the phase-frequency response reconstruction and the impulse response function time window determination. The impulse response function of a range-dependent ocean channel is modeled using the proposed method with different frequency resolutions and compared with the interpolation method and traditional Fourier synthesis method. Modeling results show that the proposed method requires only a tenth of the frequency resolution of the traditional Fourier synthesis method and the correlation coefficients of modelling output time series are preserved above 95%. The proposed method also exhibits better phase response reconstruction performances than the interpolation method when the frequency resolution equals to 1 Hz.